2017
DOI: 10.1177/1367006917728389
|View full text |Cite
|
Sign up to set email alerts
|

Cross-language correspondences in the face of change: Phonetic independence versus convergence in two Korean-Mandarin bilingual communities

Abstract: Aims and Objectives/Purpose/Research Questions: We investigate the robustness of cross-language phonetic correspondences in two bilingual communities over time, focusing on whether corresponding sounds (e.g. Mandarin /s/ and Korean /s’/) remain coupled in the face of language change, or whether the categories diverge over time in younger, more proficient bilinguals. Design/Methodology/Approach: We quantify the extent of assimilation versus independence of categories across languages by comparing bilinguals’ pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
(83 reference statements)
1
6
0
Order By: Relevance
“…This confirms similar reports of relatively large L1-L2 contrasts in young, proficient speakers: early L1 Spanish learners of L2 English showed a larger contrast between their L1 Spanish and L2 English stop consonants than late learners, 26 and young Korean-Mandarin bilinguals showed a larger contrast in COG between their Korean and Mandarin sibilants than older L1 Korean L2 Mandarin speakers. 27 The higher COG for /s/ in L2 English than in L1 Dutch corresponds with a more forward tongue position in producing English /s/ than in Dutch /s/. Similar results have been reported for vowels too, with higher formants for English vowels than for Dutch vowels, again corresponding to a more forward tongue position in producing English vowels as compared to Dutch vowels.…”
Section: Discussionsupporting
confidence: 75%
“…This confirms similar reports of relatively large L1-L2 contrasts in young, proficient speakers: early L1 Spanish learners of L2 English showed a larger contrast between their L1 Spanish and L2 English stop consonants than late learners, 26 and young Korean-Mandarin bilinguals showed a larger contrast in COG between their Korean and Mandarin sibilants than older L1 Korean L2 Mandarin speakers. 27 The higher COG for /s/ in L2 English than in L1 Dutch corresponds with a more forward tongue position in producing English /s/ than in Dutch /s/. Similar results have been reported for vowels too, with higher formants for English vowels than for Dutch vowels, again corresponding to a more forward tongue position in producing English vowels as compared to Dutch vowels.…”
Section: Discussionsupporting
confidence: 75%
“…In line with the (revised) Speech Learning Model [9,22], several studies have observed some degree of cross-language influence between the corresponding sounds in each language of a bilingual [23,24,25]. At the same time, the presence of similar or identical sounds in both languages does not necessarily entail a link between those two sounds, as similarity may only exist on the surface, masking independent sound categories across languages [26]. If Cantonese /n/ and /l/ are linked with English /n/ and /l/, then the merging of /n/ and /l/ in Cantonese should result in a similar narrowing of the acoustic distance between English /n/ and /l/.…”
Section: Introductionmentioning
confidence: 91%
“…The group-level analyses also demonstrate that cross-language differences are maintained: bilinguals' /n/ and /l/ categories are not inextricably linked across languages-English appears separate and Cantonese merged (cf. [26]). These results may, however, gloss over individual differences in the acoustic realization of these sounds, participation in or degree of merger, and cross-language links.…”
Section: Individual Differencesmentioning
confidence: 99%
“…The majority of ethnic Koreans in China are bilingual, but the dominant language is shifting from Korean to Mandarin in many communities in China (Choi, 2001;Jin, 2008;Han, 2011Han, , 2014. In particular, Schertz et al (2017) found that younger speakers in Dandong use Korean less and consider themselves to be less proficient in Korean than in Mandarin, while older speakers are dominant in Korean and have relatively low Mandarin proficiency.…”
Section: Ethnic Korean Population In Chinamentioning
confidence: 98%